CO2: A Small Ubiquitous Molecule With a Lot of Astrochemical Debate Attached - Bredehöft, Jan Hendrik (Frontiers in Astronomy and Space Sciences, 2020)
Water, carbon monoxide and carbon dioxide are the most abundant molecules in the condensed phase of interstellar dust grains. Water is formed by hydrogenation of oxygen species adsorbed on the surface of dust grains, while carbon monoxide is formed by reactions between ionized carbon and hydroxyl species in the gas phase. It is the second most abundant molecule in the gas phase after molecular hydrogen. The formation of carbon dioxide, however, cannot proceed in the gas phase as the addition of an oxygen to carbon monoxide is so exothermic that the new-formed molecule quickly breaks a C-O bond without a third body to transfer the excess energy to. It is commonly accepted that carbon dioxide is formed by energetic processing of carbon monoxide and water on grain surfaces. The exact mechanism of the oxidation of carbon monoxide and the intermediates formed in the process, however, are under some dispute. The role of the HOCO· radical in the oxidation of carbon monoxide is especially contested, as theory predicts it should not be able to dissociate the H-O bond to yield carbon dioxide, but it is experimentally observed in some studies of the reaction. The author presents here a short overview of established and recent experimental results in an attempt to reconcile seemingly contradictory results and give a comprehensive and consistent picture of the radiation induced reactions between carbon monoxide and water on grain surfaces.